1985
DOI: 10.1038/315511a0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of the platelet aggregation factor thromboxane A2

Abstract: In 1975, Hamberg et al. reported evidence for the existence of an unstable platelet-aggregating factor which they named thromboxane A2 (TXA2) and for which they proposed a novel bicyclic oxetane structure (1, below) based on the short half-life of the factor (t1/2 (37 degrees C) = 32 s at pH 7.4) and the isolation of degradation products related to thromboxane (TXB2) (2, below). As natural TXA2 has not yet been isolated and characterized as a pure compound, we have synthesized the proposed structure (1) from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(52 citation statements)
references
References 23 publications
1
50
0
1
Order By: Relevance
“…14,15 Consistent with this suggestion is the fact that an inhibitor of PLA 2 prevented AR-induced platelet isoprostane and TxB 2 formation. Of note, 2 ROS scavengers, such as SOD and vitamin C, inhibited not only AR-induced isoprostane and TxB 2 production but also AR-induced NOX2 activation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…14,15 Consistent with this suggestion is the fact that an inhibitor of PLA 2 prevented AR-induced platelet isoprostane and TxB 2 formation. Of note, 2 ROS scavengers, such as SOD and vitamin C, inhibited not only AR-induced isoprostane and TxB 2 production but also AR-induced NOX2 activation.…”
Section: Discussionsupporting
confidence: 67%
“…AR is associated in vitro and in vivo with enhanced formation of 2 platelet eicosanoids with proaggregating property, namely TxB 2 and isoprostanes. 14,15 Platelet TxB 2 formation after PCI despite concomitant low doses of aspirin suggests incomplete inhibition of platelet TxB 2 , which could favor post-PCI thrombotic complications. 19 Future studies should investigate whether a different therapeutic approach with aspirin may prevent PCI-induced platelet TxB 2 formation.…”
Section: Discussionmentioning
confidence: 99%
“…The of 20 sec at 0C and pH 7.4. This is substantially less stable than leukotriene A4 or thromboxane A2 (12,13), two of the most unstable of the evanescent family of products derived by oxygenation of polyunsaturated lipids. Our studies reported here are on the formation of allene oxides in flaxseed.…”
mentioning
confidence: 99%
“…TXA 2 is formed by the action of thromboxane synthase on the prostaglandin endoperoxide H 2 (PGH 2 ) and causes vasoconstriction, bronchoconstriction, and irreversible platelet aggregation (Hamberg et al, 1975;Svensson et al, 1976;Bhagwat et al, 1985;Fiddler and Lumley, 1990). Furthermore, recent studies have pointed out a significant stimulatory role of TXA 2 in the proliferation of vascular smooth muscle cells and mitogenesis (Pakala and Benedict, 1998;Koba et al, 2000).…”
mentioning
confidence: 99%